Enhancing sustainable waste management strategies for small and medium-sized enterprises: a focus on commercial refurbishment projects in the United Kingdom - Garoghan, Simon; Adewumi, Ayomikun Solomon; Ofetotse, Eng L.; Onyango, Vincent; Dawodu, Ayotunde (Frontiers in Built Environment, 2025)
With commercial refurbishment projects being identified as large contributors to landfill waste in the United Kingdom (United Kingdom), the aim of this paper is to identify effective Sustainable Waste Management strategies that could be implemented by Small and Medium-sized Enterprise (SME) construction businesses, specifically within the commercial refurbishment sector. The study adopted a mixed method approach engaging industry professionals working within SMEs through both questionnaires and interviews. Findings showed that although SME businesses aspire to make improvements, the construction industry is not making clients and consultants equally accountable. However, some of the most effective tactics that could be employed were low cost and easy to implement but it seems that some SME businesses are still averse to them for mostly economic reasons suggesting for better enlightenment of collaborative procurement routes, implementing sustainability regulations and comprehensive engagement of SMEs by industry authorities; substantial improvements can be made in the realm of sustainable waste management.